Urine and Serum Concentrations of Inhaled and Oral Terbutaline - Elers, J.; Hostrup, M.; Pedersen, L.; Henninge, J.; Hemmersbach, P.; Dalhoff, K.; Backer, V. (International Journal of Sports Medicine, 2012)
We examined urine and serum concentrations after therapeutic use of single and repetitive doses of inhaled and supratherapeutic oral use of terbutaline. We compared the concentrations in 10 asthmatics and 10 healthy subjects in an open-label, cross-over study with 2 mg inhaled and 10 mg oral terbutaline on 2 study days. Further, 10 healthy subjects were administrated 1 mg inhaled terbutaline in 4 repetive doses with total 4 mg. Blood samples were collected at baseline and during 6 h after the first inhalations. Urine samples were collected at baseline and during 12 h after the first inhalations. Median (IQR) urine concentrations peaked in the period 0–4 h after inhalation with Cmax 472 (324) ng/mL in asthmatics and 661 (517) ng/mL in healthy subjects, and 4–8 h after oral use with Cmax 666 (877) ng/mL in asthmatic and 402 (663) ng/mL in healthy subjects. In conclusion we found no significant differences in urine and serum concentrations between asthmatic and healthy subjects. We compared urine and serum concentrations after therapeutic inhaled doses and supratherapeutic oral doses and observed significant statistical diffences in both groups but found it impossible to distinguish between therapeutic and prohibited use based on doping tests with urine and blood samples.
Keywords: beta2-agonists; terbutaline; pharmacokinetics; doping; urine